Procedure for Termination of Employment Relations in The Pancasila Industrial Relations Concept - Saragih, Minggu; Mansar, Adi; Hanifah, Ida (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In the Pancasila Industrial Relations concept, the rights and responsibilities of employers and workers in a work relationship are balanced. This balance is achieved not based on considerations of strength (overall influence), but based on feelings of justice and honor. In addition, Pancasila Industrial Relations believes that company results achieved through cooperation between workers and entrepreneurs must be enjoyed equally by taking into account the sacrifices made by each individual. When a work stoppage occurs, this method is also assisted through a component that is a marker of Pancasila standards in legal guidelines through Law Number 2 of 2004 concerning Settlement of Industrial Relations Problems. This research employed normative juridical research methods Referring to Government Regulation Number 35 of 2021 concerning Specific Time Work Agreements, Outsourcing, Working Time and Rest Time and Termination of Employment Relations, if there is termination of employment in accordance with the reasons for Termination of Employment, then the formulation of the amount of rights that the worker has at the time of termination of employment work adjusted to the reason for termination of employment. As the government's response to the difficulties and dynamics of competency and productivity-based employment relationships, this regulation was promulgated to provide guidelines for ending employment relationships because it is very necessary in efforts to protect rights and government assistance in fulfilling the welfare of workers/employees both during work, especially after the end of work friendships